Drugs and drug control in Zimbabwe - Matunhu, Jephias; Matunhu, Viola (Routledge, 2021)
This chapter examines the drug situation in Zimbabwe in the context of the mainstream illegal substances such as cannabis, it assigns similar weight to legal substances, which are easily accessible and can also be dangerous to health. In Zimbabwe, drug abuse is pronounced among youths and the most abused drugs by these youths include alcohol, tobacco and mbanje, petrol, lysergic acid diethylamide, and benzoldiazepines. Peer pressure is considered an influential factor in drug abuse in Zimbabwe. Many drug abusers begin experimenting with drugs during their teens. Tobacco is one of the most abused substances in Zimbabwe, and one of the reasons for this is that it is the mainstay of the Zimbabwean economy. The desire to increase agricultural productivity in Zimbabwe has influenced use of agricultural chemicals. Statistical analysis of crime records in Zimbabwe indicates that there is an increase in the trafficking and abuse of illicit drugs in the country.